Examining funding flows and their influence on maternal health outcomes: a case study of Samburu County - Napunyu, N. (Strathmore University, 2024)
Funding challenges are common in healthcare institutions in developing nations. In many low- and middle- income countries, health financing is fragmented, relying on multiple payment methods from various purchasers. This affects the efficiency and effectiveness of healthcare delivery. Inadequate funding can hinder access to quality healthcare, resulting in poor service delivery and health outcomes. This issue is evident in Kenya, where unpredictable funding flows compromise health service delivery, especially in critical areas like maternal and child health. The study aimed to assess funding flows to public health facilities in Samburu County and their impact on healthcare provider behaviour and maternal health outcomes. A qualitative research design was used, employing purposive sampling to select participants. Data were collected through semi-structured questionnaires, in-depth interviews, and focus group discussions with county officials, healthcare providers and Samburu women. Thematic analysis was used to identify patterns and themes in the qualitative data. Findings indicate that Samburu County receives limited public funding, leading to resource constraints in healthcare facilities. This affects the availability of essential medical supplies, infrastructure, and personnel. Out-of-pocket expenditures remain significant, creating financial barriers to maternal healthcare, especially for low-income households. Despite funding constraints, some healthcare providers demonstrated positive behaviours, such as adherence to clinical guidelines, patient-centred care, professionalism, empathy, and effective communication, promoting good health outcomes. However, negative behaviours like absenteeism, negligence, corruption, and mistreatment of mothers were also reported. Challenges related to funding flows included inadequate resources for training healthcare workers, low remuneration, and poor working conditions, all contributing to poor maternal health outcomes. Cultural factors and hierarchical management structures also influenced provider-patient interactions. The study concluded that consistent funding flows could improve healthcare provider behaviours and maternal health outcomes, reducing maternal morbidity and mortality rates, disease burden, and enhancing the quality of life. The findings will inform policymakers and program managers to develop strategies for improving funding flows, ultimately enhancing service delivery for maternity care and improving maternal health outcomes.
Full - text thesis